The Effect of Crane Performance and Loading/Unloading Productivity on Sales Growth at PT Jakarta International Container Terminal - Gunawan, Indra; Agusinta, Lira; Saribanon, Euis (Dinasti International Journal of Digital Business Management, 2025)
The background of this study is based on the critical role of the logistics sector, particularly ports, in supporting the national economy through cost efficiency and increased competitiveness. However, data shows that PT JICT's sales growth declined from 2014 to 2018, indicating problems in maritime transport management, particularly in port operations. The decline in crane performance and fluctuations in loading and unloading productivity are suspected to be the main factors causing this decline in sales growth. Low crane performance slows loading and unloading, while unstable loading and unloading productivity hinder the effectiveness of port services. This study aims to analyze the effect of crane performance and loading and unloading productivity on sales growth at PT Jakarta International Container Terminal (JICT). Therefore, this study was conducted to empirically determine the extent to which crane performance and loading and unloading productivity affect sales growth at PT JICT, with the hope that the results will serve as a basis for evaluating and improving port operational management. This study aims to analyze the effect of crane performance and loading and unloading productivity on sales growth at PT Jakarta International Container Terminal (JICT). Therefore, this study was conducted to empirically determine the extent to which crane performance and loading and unloading productivity affect sales growth at PT JICT, with the hope that the results can serve as evaluation material and a basis for improving port operational management. This study uses a quantitative method, SEM-PLS analysis. The results show that crane performance has a positive, highly significant effect on sales growth at PT Jakarta International Container Terminal, while loading and unloading productivity also has a positive, significant impact on sales growth. However, crane performance does not have a direct or indirect effect on loading and unloading productivity, and loading and unloading productivity does not mediate the relationship between crane performance and sales growth.